PERSEPSI WARGA KAMPUS STAIN DATOKARAMAPALU TENTANG PENCIPTAAN SUASANA RELIGIUS KAMPUS UNTUK MENUNJANG PENCAPAIAN KUALITAS AKADEMIK (Menyongsong Alih Status Kelembagaan STAIN Menjadi IAIN) - Mokh. Ulil Hidayat (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
Campus religiousity is associated with religious activities on campus. Creating a campus religiosity is very important because it strongly supports the religious atmosphere of academic quality which produces of academic achievement. To create the atmosphere of the campus religiousity there are some important points, namely; variable of institutional vision which becomes a brand mark, the students` understanding, the existence of clear rules and agreed upon, and exemplary leadership and faculty